Biological and psychological monitoring of training status during an entire season in top kayakers - Garatachea, N.; Garcia-Lopez, D.; Jose Cuevas, M.; Almar, M.; Molinero, O.; Marquez, S.; Gonzalez-Gallego, J. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM:The aim of this study was to analyze changes in selected biological and psychological variables in a group of top level kayakers along a 42-week training season. METHODS:Eight top junior sprint kayakers (age=16.8±2.1) (5 men and 3 women) with international competitive experience participated in the research. During the 42-wk season the subjects were tested in three occasions: (T1) in the second week of the general training period, (T2) at the beginning of the specific training period, (T3) at the beginning of the competitive training period. Firstly, subjects were asked to complete the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport) and the Profile of Mood States (POMS) questionnaires, and Borg´s rate of perceived exertion scale (RPE). Immediately after, blood samples were collected and white blood cells, creatine kinase (CK), C-reactive protein (CRP), myeloperoxidase protein levels (MPO) and glutathione status were determined. ANOVA with repeated measures was used to determine the differences between tests. RESULTS:From the hematological and biochemical measures only total leukocytes changed significantly, increasing at T3 when compared to T1. There were no differences along the entire season in both RESTQ-Sport and POMS scores or indices. Concerning performance, the group improved their maximal strength (+17.4% in bench-press 1RM) and their specific-distance time (+9.8%). The main finding of the present study was that training was well-balanced between stress and recovery because while specific performance increased, signs of overtraining were not found. CONCLUSION: Training monitoring in athletes should be performed in a multilevel approach using measurements of performance as well as biological or psychological parameters.